2004
DOI: 10.1039/b312682j
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of 3-acetoacetylaminobenzo[b]furan derivatives having cysteinyl leukotriene 2 receptor antagonistic activity

Abstract: Novel 3-acetoacetylaminobenzo[b]furan derivatives having a modified triene system at the 3-position were synthesized starting with 3-aminobenzo[b]furans. The enol isomers, 3-[(3-hydroxybut-2-enonyl)amino]benzo[b]furans (), of the 3-acetoacetylaminobenzo[b]furans were obtained as stable isomers owing to formation of a hydrogen bonding between the enol hydroxyl group and the amidocarbonyl group. The planarity of the C-2 substituent through the C-3 side chain suggested the existence of a modified conjugational tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…SERMs are characterized by at least two common structural features, a phenolic hydroxyl group and a phenoxyethylamino group (phenyl-OCH 2 CH 2 N-). 14a,b,d We recently reported that the compound 4 15 prepared in our current studies displayed very potent anti-bone resorption activity in vitro and exhibits a potent anti-osteopenic effect in vivo. 14c It has also been suggested to influence the endometrial properties of SERMs in women by the antiestrogenic side chain.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…SERMs are characterized by at least two common structural features, a phenolic hydroxyl group and a phenoxyethylamino group (phenyl-OCH 2 CH 2 N-). 14a,b,d We recently reported that the compound 4 15 prepared in our current studies displayed very potent anti-bone resorption activity in vitro and exhibits a potent anti-osteopenic effect in vivo. 14c It has also been suggested to influence the endometrial properties of SERMs in women by the antiestrogenic side chain.…”
Section: Introductionmentioning
confidence: 53%
“…16 Both the compound 4 15 and (E)-(8-bromo-(E)-2-aralkenylbenzo[b]furo[3,2d] [1,3]oxazin-4-ylidene)acetaldehydes (5) possess the phenoxyethenylamino moiety through the furan oxygen atom and the nitrogen atom. 16 Both the compound 4 15 and (E)-(8-bromo-(E)-2-aralkenylbenzo[b]furo[3,2d] [1,3]oxazin-4-ylidene)acetaldehydes (5) possess the phenoxyethenylamino moiety through the furan oxygen atom and the nitrogen atom.…”
Section: Introductionmentioning
confidence: 99%
“…The two benzofurane and benzothiophene precursors ( 3 and 4 ) were obtained by methods previously described in the literature . Subsequently, 3‐amino‐2‐cyanobenzofurane 3 was prepared by treatment of 2‐hydroxybenzonitrile with bromoacetonitrile in dimethylformamide.…”
Section: Resultsmentioning
confidence: 99%
“…Biological Activity The benzo[b] furan compounds pre- Chart 2 pared in this work were evaluated for their cysLT1 and cysLT2 inhibitory activities by measuring their inhibition of agonist-induced calcium release according to the method reported by Nothacker. 11,12,32) Inhibitory activities of seven 2-thienylbenzo[b] furans (5b, d, 6a-e) were shown in Table 1. The 2-cyano-3-hydroxy-2-butenamide (6a) and the butyric acid 6b showed more than 40% inhibition of calcium mobilization in cysLT1 cells.…”
Section: Preparation Of 2-isoxazolylbenzo[b] Furans (9-12)mentioning
confidence: 99%
“…4) However, no selective cysLT2 antagonist has yet been developed for clinical applications. Recently, increased expression of cysLT2 receptor has been reported in colon cancer 9) and myocardial ischemia-reperfusion injury.10) The development of a dual antagonist and/or selective cysLT2 antagonist should be of great therapeutic value.In previous papers, we reported the preparation of sev-furan derivatives (A) and their cysLT1 and cysLT2 inhibitory activities 11,12) (Fig. 2).…”
mentioning
confidence: 99%